Disastrous Mechanism and Concentration Distribution of Gas Migration in Fully Mechanized Caving Stope in Wuyang Coal Mine - Li Chong; He Sifeng; Xu Zhijun (Geofluids)
The overrunning disaster of harmful gas tends to occur in the working face in thick coal seam with high gas concentration, as the fully mechanized caving stope has the characteristics of high mining intensity, high remnant coal, and high gas content. Therefore, the disastrous mechanism and concentration distribution of gas migration in fully mechanized caving stope are the theoretical basis for gas control scheme. Based on the 7607 working face in Wuyang coal mine, the gas emission quantity in working face is comprehensively analyzed by field measurement in this paper. The gas leakage field, oxygen concentration field, and gas concentration field in 7607 working face are simulated by establishing the equal proportional numerical model. Due to the increase of air leakage in working face caused by the high alley pumping drainage, the risk of coal spontaneous combustion is also analyzed, when gas extraction in goaf is carried out. The research results show that the gas drainage technology in high drainage roadway has a remarkable effect on the gas overrunning phenomenon. The gas concentration near the upper corner of the working surface has been reduced from 0.7%-1% to 0.5%. At the same time, it is necessary to pay attention to the risk of coal spontaneous combustion in the goaf for gas drainage in the high drainage roadway. The width of the oxidation zone in the goaf is about 25 m deeper than that before the drainage. Research results provide the references for gas control technology and coal spontaneous combustion prevention in similar working faces.